2017
DOI: 10.1177/1362361317709603
|View full text |Cite
|
Sign up to set email alerts
|

Hooked on a feeling: Repetitive cognition and internalizing symptomatology in relation to autism spectrum symptomatology

Abstract: Repetitive cognition, including rumination such as that seen in depression, has been shown to correlate with depression symptoms in both typically developing individuals and individuals with autism spectrum disorder. Repetitive cognition is more common in autism spectrum disorder than in typically developing peers, as is depression; thus, this study evaluated the role of repetitive cognition in relation between autism spectrum symptomatology and depressive symptomatology. In all, 200 typically developing adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
4
16
0
Order By: Relevance
“…This finding is consistent with studies reporting an association between rumination and ASD symptoms of RRBs such as insistence on sameness and perseveration (Gotham et al 2014;Pugliese et al 2015). However, a recent study of adults in the general population did not find an association between sadness-focused rumination and perseveration using a self-report measure of ASD symptoms (Keenan et al 2017). Our finding of an association between anger rumination and RRBs in ASD is noteworthy because RRBs such as rigidity of thinking, insistence on sameness, and perseveration are part of the constellation of core ASD symptoms and could predispose children with ASD to engage in rumination through greater difficulty in disengaging from perseverative, ruminative thoughts focused on the stressor (Mazefsky et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with studies reporting an association between rumination and ASD symptoms of RRBs such as insistence on sameness and perseveration (Gotham et al 2014;Pugliese et al 2015). However, a recent study of adults in the general population did not find an association between sadness-focused rumination and perseveration using a self-report measure of ASD symptoms (Keenan et al 2017). Our finding of an association between anger rumination and RRBs in ASD is noteworthy because RRBs such as rigidity of thinking, insistence on sameness, and perseveration are part of the constellation of core ASD symptoms and could predispose children with ASD to engage in rumination through greater difficulty in disengaging from perseverative, ruminative thoughts focused on the stressor (Mazefsky et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to results in non-ASD populations (Aldao et al 2010), associations between rumination and internalizing symptoms of anxiety and depression were also found in children Patel et al 2017;Pouw et al 2013) and adults (Crane et al 2011;Gotham et al 2014;Keenan et al 2017) with ASD. Two recent studies reported an association between anger rumination, core ASD symptoms, and disruptive behaviors (Patel et al 2017;Pugliese et al 2015).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The tendency toward repetitive cognition in ASD may increase susceptibility to perseveration on distressing stimuli (Gotham et al, 2015; Keenan et al, 2018; Mazefsky et al, 2012). Indeed, initial evidence suggests that individuals with ASD experience increased neural reactions to negative stimuli in comparison to typically developing (TD) controls (e.g.…”
mentioning
confidence: 99%
“…Tottenham et al, 2014). Sustained processing of negative stimuli can have adverse downstream effects on mental health (Gotham et al, 2015; Keenan et al, 2018). Keenan et al (2018) found that perseveration mediated the relationship between ASD symptoms and depression symptoms in a sample of TD adults.…”
mentioning
confidence: 99%